FEATURES OF ANATOMICAL STRUCTURE AND PHYSIOLOGY OF DONKEY HOOVES - Sakharova, O. U. (Scientific Progress & Innovations, 2021)
There is almost no information in the Ukrainian literature on the anatomical and physiological features of donkey hooves, their differences from horses’ hooves, methods of trimming and the development of hoof pathologies. Due to the popularization of donkey keeping not only as a farm animal, but also as a pet, for-eign scientists have increased interest in donkeys including their hooves. The review of foreign papers has shown that all structural elements of donkey hooves have anatomical and physiological differences from horses' hooves. Among such differences, there are the following: frontal shape of the hoof, the shape of the supporting hoof surface, other measurements of the hoof angles, the size and position of the hoof bones, large developed turgid hoof parts, different ratio of hoof structures and others. Therefore, the hooves of don-keys require different methods of hoof care. Donkeys, unlike horses, are able to hide the existing hoof prob-lems for a long time, and clinical signs appear when the condition of hooves is too complicated, and treat-ment and rehabilitation will be long and expensive. In this review, the differences between the main ratios in the anatomical structures of donkey hooves and horse hooves were generalized. This knowledge will help to do the correct cleanng of donkey hooves. An important feature of donkeys is the different functioning of the hoof mechanism, which will work properly only at the correct anatomical structure of donkeys hooves. The histological structure of donkey hooves also has its own peculiarities. All the data presented in this article should be taken into account in the routine care of donkey hooves and in the treatment and rehabilitation of their pathologies. Therefore, owners and veterinary doctors dealing with donkeys need to know for sure what normal donkey hooves are to be like and how they differ from horse hooves.